Vitamin D status and mortality in chronic kidney disease - Pilz, Stefan; Tomaschitz, Andreas; Friedl, Claudia; Amrein, Karin; Drechsler, Christiane; Ritz, Eberhard; Boehm, Bernhard O.; Grammer, Tanja B.; März, Winfried (Nephrology, dialysis, transplantation, 2011)
BACKGROUND: Vitamin D deficiency is found in the majority of patients with chronic kidney disease (CKD) and may contribute to various chronic diseases. Current guidelines suggest correcting reduced 25-hydroxyvitamin D [25(OH)D] concentrations in CKD patients with an estimated glomerular filtration rate (eGFR) <60 mL/min/1.73 m(2). Whether low 25(OH)D levels in these patients are associated with higher mortality is unclear. This issue was addressed in the present work. - METHODS: We examined 444 patients with eGFR <60 mL/min/1.73 m(2) from the Ludwigshafen Risk and Cardiovascular Health Study. This prospective cohort study includes Caucasian patients without primary kidney disease who were routinely referred to coronary angiography at baseline (1997-2000). - RESULTS: During a median follow-up time of 9.4 years, 227 patients died including 159 deaths from cardiovascular causes. Multivariate adjusted hazard ratios (HRs) (with 95% confidence intervals) in severely vitamin D-deficient [25(OH)D <10 ng/mL] compared to vitamin D-sufficient patients [25(OH)D ≥ 30 ng/mL] were 3.79 (1.71-8.43) for all-cause and 5.61 (1.89-16.6) for cardiovascular mortality. Adjusted HRs per 10 ng/mL increase in 25(OH)D levels were 0.63 (0.50-0.79) for all-cause and 0.59 (0.45-0.79) for cardiovascular mortality. There was no significant interaction with parathyroid hormone concentrations. - CONCLUSIONS: Low 25(OH)D levels are associated with increased all-cause and cardiovascular mortality in CKD patients. These findings support suggestions to correct vitamin D deficiency, but whether vitamin D supplementation improves survival remains to be proven in randomized controlled trials.